Syntrophic degradation of fatty acids by methanogenic communities - Stams, Alfons Johannes Maria (2012)
In methanogenic environments degradation of fatty acids is a key process in the conversion of organic matter to methane and carbon dioxide. For degradation of fatty acids with three or more carbon atoms syntrophic communities are required. This chapter describes the general features of syntrophic degradation in methanogenic environments and the properties of the microorganisms involved. Syntrophic fatty acid-degrading communities grow at the minimum of what is thermodynamically possible and they employ biochemical mechanisms to share the minimum amount of chemical energy that is available. Aggregation of the syntrophic fatty acid-degrading communities is required for high rate conversion.